Northern hemisphere summer insolation and ice volume driven variations in hydrological environment in southwest China - Wu, Yao; Warken, Sophie F.; Frank, Norbert; Mielke, Aaron; Chen, Chao-Jun; Li, Jun-Yun; Li, Ting-Yong (Geophysical research letters, 2023)
The interpretation of stalagmite δ18O in terms of reflecting Asian summer monsoon (ASM) precipitation is still elusive. Here, we present high-resolution stalagmite trace element ratios (X/Ca, X = Mg, Sr, Ba) records from southwest China covering 116.09 to 4.07 ka BP. δ18O, δ13C, and X/Ca values exhibit clear precessional cycles, with δ18O values reflecting ASM circulation/intensity, while X/Ca ratios capture local precipitation or evapotranspiration variations. Our results show that Northern Hemisphere summer insolation (NHSI) is the main driver of ASM intensity and precipitation phase variation, but global ice volume modulates the response magnitude of summer precipitation to insolation. During the Last Glacial Maximum, high ice volumes caused significant monsoon precipitation to decrease. In contrast to modern observations of the tripolar distribution of precipitation in China, our record is consistent with paleo-precipitation records in southern and northern China.
Online veröffentlicht: 29. November 2023
Gesehen am 14.05.2024